Ultra-brief acceptance & commitment therapy for inpatients with psychosis - a single-case experimental design investigating processes of change - Muñoz González-Deleito, Carmen; McCracken, Lance M.; Tyrberg, Mårten J. (Cognitive behaviour therapy, 2024)
People with primary psychosis are among the most seen in inpatient psychiatry. Treatment guidelines recommend both pharmacological and psychological treatments. However, psychological treatments are not routinely offered in many settings. There is also a lack of research on psychological treatments for this vulnerable population in the inpatient setting. The first aim of the current study was to examine treatment effects of a brief form of Acceptance and Commitment Therapy on outcomes valued by the treatment recipients. The second aim was to explore hypothetical processes of change in relation to outcomes over time. Three people with primary psychosis were treated for two to four sessions. A replicated single-case experimental design with multiple baselines across subjects (Clinical Trials registration number ID NCT04704973) was employed to examine treatment effects. The Personal Questionnaire (PQ) was used as primary outcome, symptom believability and preoccupation as proposed processes of change. Data were analyzed using visual inspection, calculation of Tau-U values, and cross-lagged correlation. All participants improved significantly on PQ and the symptom preoccupation measure. Two improved significantly on the symptom believability measure. Cross-lagged correlation analyses showed no clear mediation. Change in proposed processes of change and primary outcome predominantly happened concomitantly, although patterns of results reflected individual differences.